Da’wah Strategy for Jabatan Hal Ehwal Agama Islam Negeri Sabah (JHEAINS) in the Tuaran Region Towards Muallaf - Jusup, Nurshaiera Binti (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2023)
Jabatan Hal Ehwal Islam Negri Sabah (JHEAINS) is a da'wah organization that operates in society. This research aims to discover the da'wah strategy used by the Tuaran section of JHEAINS in its da'wah efforts against Muslim converts. This research analyses the methods, approaches and obstacles to JHEAINS' da'wah towards Muslim converts. The technique used in this research is descriptive; this method aims to systematically describe specific facts factually and carefully using observation, interviews and documentation techniques. The research results show that JHEAINS uses several da'wah methods with Fardhiyyah, tarbiyyah, al-Ardiyyah, al-Bi'thiyyah, al-Mujadalah and counselling approaches. Even so, the JHEAINS organization faces several obstacles in preaching to Muslim converts. This research has significant implications, especially for converts and preachers in the JHEAINS organization spreading da'wah in Tuaran.